Assessment and Evaluation in Active Learning Implementations: Introducing the Engineering Education Active Learning Maturity Model - Humberto Arruda; Édison Renato Silva (MDPI AG, 2021)
With the technological changes experienced in the world in recent decades, society has changed as a whole, due to the speed and availability of information that exists today. As student attention decreases, critical thinking and Active Learning, which places the student at the center of the learning process, have gained prominence. Considering the growing popularity of these techniques, this article proposes the Engineering Education Active Learning Maturity Model (E2ALM2), a framework that allows practitioners to assess the current maturity of Active Learning implementation in a program or a course. E2ALM2 was built from a literature review of key success factors (KSF) for Active Learning implementations, which were divided into dimensions. Each KSF is composed of constructs, which are detailed with variables. Each variable has a proposed measurement method and an estimated uncertainty level. The framework can support diagnosis and practical improvements in real settings.